Pore scale modeling on dissociation and transportation of methane hydrate in porous sediments. (15th December 2021) - Song, Rui; Sun, Shuyu; Liu, Jianjun; Yang, Chunhe
Abstract: Fundamental study on the pore scale dissociation and transportation mechanism of methane hydrate in porous sediments contributes to understanding the heat and mass transfer in the multiple physicochemical and thermal processes. This paper proposes a novel enthalpy-porosity technique coupling with volume of fraction (VOF) method for modeling the phase-change process of the hydrate dissociation and the multi-phase flow. The mathematical models are programed by C language and used as the subroutine for the commercial FLUENT software. The proposed theoretical model is validated by comparison with the experiment and numerical modeling in literature. The distribution of fluid saturation, velocity and temperature in the MH dissociation are presented, analyzed and discussed comparatively. As the first effort in literature, the proposed model can properly simulate the effects of the phase change on the pore structure evolution, multiphase flow, heat and mass transfer and kinetic reaction process in porous media in real-time. Both the normalized permeability of water ( K Nw ) and the normalized absolute permeability ( K N ) of the porous media with different hydrate saturation are acquired and analyzed comparatively with the results in the previous studies. This study provides a new insight into pore scale modeling on the multiphase flow with phase change. Highlights: The coupling enthalpy-porosity with VOF is proposed to model hydrate dissociation. Pore structure evolution, heat & mass transfer in MH dissociation are studied. K Nw and K N of the porous media with different hydrate saturation are acquired. New insight into pore scale multiphase flow with phase change is achieved.